Prognostic indicator tools in COPD: a systematic review. Issue Volume 2:Issue (2012)Supplement 1 (1st March 2012) - Firth, Adam; Frank, Tim; Sanders, Caroline
Abstract : Background: Patients with severe chronic obstructive pulmonary disease have a burden of symptoms at least equivalent to that of patients with terminal cancer yet palliative care provision is less well established. A significant obstacle to providing palliative care for patients with COPD is the challenge associated with identifying those at risk of death when the condition is associated with such an unpredictable illness trajectory. Prognostic indicator tools may help overcome this but no systematic review has considered the utility of COPD specific prognostic indicator tools in primary care settings. Aim: To explore whether multidimensional prognostic indicator tools in COPD can predict 12-month mortality in patients being managed in primary care. Methods: This systematic review employs the discipline of narrative synthesis following the approach recommended by the Centre for Reviews and Dissemination (CRD). An extensive search incorporating relevant conference proceedings was conducted, followed by data extraction through tabulation, quality assessment by two researchers and synthesis of available data. Results: 22 individual tools were identified from 37 relevant papers. Four tools: the ADO index, HADO score, DOSE index and TARDIS were developed with a specific focus on primary care. Only the BODE index had been validated in sufficient cohorts for its efficacy to be confidently established; however the BODE index, with its 6-min walking test, lacks utility in primary care settings. No studies have assessed the prognostic approach currently recommended in UK clinical practice. Conclusions: No current multidimensional prognostic indicator tools are sufficiently validated to be recommended for widespread use in UK primary care to identify patients at risk of death in the next 12-months. The research conducted to date suggests that there is scope to further validate some of the proposed tools and more work is required to understand the accuracy and applicability of prognostic indicator tools for use in COPD.